Islamic Values-Based Public Relations Management in Building Trust and School Image: A Case Study at MTs Ar-Rois Cendekia Semarang - Saeda Aliatus Zaman; Fatkuroji Fatkuroji; Agus Sutiyono; Mohd Huefiros Efizi bin Husain (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study is designed to examine how Public Relations management is implemented in improving the institutional image and strengthening the relationship between schools and their stakeholders at MTs Ar-Rois Cendekia Semarang. In the context of contemporary education, Public Relations serves as a strategic bridge that connects educational institutions with the community through communication, publications, and collaborative efforts that foster public trust. At MTs Ar-Rois Cendekia, PR management is based on Islamic values, with a strong emphasis on ethical communication, information transparency, and service practices that reflect the character of the religion. This research uses a qualitative approach, collecting data through direct observation and structured interviews involving madrasah leaders, public relations personnel, teachers, and school committee members. The results of the study show that the PR strategies implemented include personal branding initiatives, the use of digital media platforms, and collaborative programs with stakeholders such as local authorities and the surrounding community. Islamic principles serve as the ethical foundation for all Public Relations activities. Although there are still challenges, including limitations in the management of human resources and digital media, Public Relations at MTs Ar-Rois Cendekia continues to carry out its functions effectively in strengthening a positive image and fostering harmonious relationships between schools and communities. This research also speculates on the contribution to the development of Islamic educational management studies by enriching the conceptual framework of educational PR management that integrates with Islamic values in institutional practice.